Organic chemicals in the environment mechanisms of degradation and transformation - Neilson, Alasdair H.; Allard, Ann-Sofie. (Boca Raton, Fla. : CRC Press, 2013)
"This fully updated second edition addresses the persistent environmental threat of organic chemicals with a fresh approach to evaluating degradation and transformation processes. It examines a wide range of chemical as well as abiotic and microbiological reactions mediated by microorganisms. Emphasizing the pathways used and the broad classes of enzyme involved, it provides an overview of experimental procedures with detailed coverage of xenobiotic organic compounds. Updated topics include enantiomers and racemization, dehalorespiration, caffeate as electron acceptor, reduction of carbocyclic rings, steroid degradation, corrins, glutathione, and pyridoxal-P"--
section 1. Degradation and transformation processes -- section 2. Experimental procedures -- section 3. Pathways and mechanisms of degradation and transformation.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Aquatic organisms -- Effect of water pollution on; Organic water pollutants -- Environmental aspects; Electronic books